2008
DOI: 10.1071/ea07244
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of greenhouse gas emissions from Australian feedlot beef production using open-path spectroscopy and atmospheric dispersion modelling

Abstract: Feedlot production of beef cattle results in concentrated sources of gas emissions to the atmosphere. Reported here are the preliminary results of a micrometeorological study using open-path concentration measurements to determine whole-of-feedlot emissions of methane (CH4) and ammonia (NH3). Tunable near-infrared diode lasers were used to measure line-averaged (150–400 m) open-path concentrations of CH4 and NH3. A backward Lagrangian stochastic model of atmospheric dispersion and the software package WindTrax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 7 publications
3
46
0
Order By: Relevance
“…Invalid data can be generated as a result of misalignment of the laser, unfavourable wind directions, surface roughness or periods in which the atmospheric conditions (rain, fog, heat waves, etc.) are unsuitable for applying the model (Freibauer 2000 ; Laubach and Kelliher 2005 ;Loh et al 2008 ). To optimize the positioning of the equipment, these meteorological and physical aspects of the experimental site must be taken into account (Flesch et al 2007 ;Loh et al 2008Loh et al , 2009 ).…”
Section: Open-path Lasermentioning
confidence: 99%
“…Invalid data can be generated as a result of misalignment of the laser, unfavourable wind directions, surface roughness or periods in which the atmospheric conditions (rain, fog, heat waves, etc.) are unsuitable for applying the model (Freibauer 2000 ; Laubach and Kelliher 2005 ;Loh et al 2008 ). To optimize the positioning of the equipment, these meteorological and physical aspects of the experimental site must be taken into account (Flesch et al 2007 ;Loh et al 2008Loh et al , 2009 ).…”
Section: Open-path Lasermentioning
confidence: 99%
“…Laubach et al (2008) clearly describe three paddockscale micrometeorological methods for measuring emissions from beef cattle. Specifically, one methodology based on inverse dispersion (Flesch et al, 2005) has been shown to have potential for estimating CH 4 emissions from feedlot and grazing production systems Kelliher, 2005a and2005b;McGinn et al, 2007 andLoh et al, 2008). This methodology has now been used across a number of grazing systems in northern Australia to determine herd-scale CH 4 emissions.…”
Section: Beef Cattle Ch 4 Emissions In Tropical Pasturesmentioning
confidence: 99%
“…It is considered to be currently among the most accurate micrometeorological techniques to calculate dispersion and determine emission rates (Denmead, 2008;Laubach, 2010;Loubet et al, 2010). It has been applied to assess methane and/or NH 3 emissions from agricultural fields fertilised with slurry (Sanz et al, 2010) and urea (Sommer et al, 2005), grazed fields (Denmead et al, 2004;Laubach and Kelliher, 2005;Laubach et al, 2008;Laubach, 2010), cattle feedlots McGinn et al, 2007;van Haarlem et al, 2008;Loh et al, 2008), and even complete farms (Flesch et al, 2009). The bLS calculates emissions accurately provided homogeneously emitting source areas (or well represented point sources), a precise monitoring of c bgd and a largely undisturbed wind field, i.e.…”
Section: Uncertainty Of the Bls/ftir Approachmentioning
confidence: 99%